2016
DOI: 10.19082/3042
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting length of stay in teaching hospitals of a middle-income country

Abstract: IntroductionThe length of stay (LOS) in hospitals is a widely used and important criteria for evaluating hospital performance. The aim of this study was to determine factors affecting LOS in teaching hospitals of Qazvin Providence.MethodsIn this cross-sectional study, patients’ health records were randomly selected from archives in teaching hospitals of Qazvin in 2013. Data were collected through a data entry form and were analyzed using Kolmogorov–Smirnov, Kruskal–Wallis, and Mann–Whitney U tests at the signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 21 publications
8
27
0
Order By: Relevance
“…This study revealed that length of hospital stay was higher in those patients who had history of surgery. This result was in line with studies done in Tabriz Shahid Madani Cardiovascular Hospital [26], Iran [27]. This could be due to history of surgery might affect the current disease recovery rate and could lead to low immunity.…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed that length of hospital stay was higher in those patients who had history of surgery. This result was in line with studies done in Tabriz Shahid Madani Cardiovascular Hospital [26], Iran [27]. This could be due to history of surgery might affect the current disease recovery rate and could lead to low immunity.…”
Section: Discussionsupporting
confidence: 91%
“…Our ratio of male to female patients is matching the UK national data for primary Total hip Replacement. The results of one study showed that the mean LOS was higher among patients with medical treatment compared with those with surgical intervention only [22] . Among other patient related factors Higher ASA PS grades have strong association for longer LOS.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Length of care of both disease in the hospital will vary depend on several factors, such as institutional factors, the severity of the disease, social factors, psychological factors, adherence and nutritional status. 20,21 Length of care was associated with high cost and burden on family of the patients. 20 National health insurance helps lower the cost of health burden of patients/family, and subsequently increases the patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%